94.7k views
1 vote
Elimination method 5x+3y=-6 -4x-5y=-3

1 Answer

2 votes

Answer:

The correct answer is (-3, 3)

Explanation:

In order to use the elimination method, multiply the top equation by 4 and the bottom equation by 5. Then add them together.

20x + 12y = -24

-20x - 25y = -15

------------------------

-13y = -39

y = 3

Now that we have the value of y, we can plug it into either equation to get the final answer.

5x + 3y = -6

5x + 3(3) = -6

5x + 9 = -6

5x = -15

x = -3

User Intra
by
5.9k points